2022
DOI: 10.1002/jvc2.57
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal comparative study by in vivo harmonic generation microscopy: Q‐switched ruby laser versus picosecond 532‐nm Nd: YAG laser for the treatment of solar lentigines

Abstract: Background: Nanosecond quality-switched ruby laser (QSRL) and frequencydoubled 532-nm picosecond Nd:YAG laser (532-nm picosecond Nd: YAG laser [PSNYL]) are well-documented treatments for solar lentigines (SLs). However, no studies have longitudinally tracked the microscopic findings before and after QSRL and 532-nm PSNYL treatment for SL removal.Objectives: To compare the clinical efficacy and dynamic histological changes between QSRL and 532-nm PSNYL in the treatment of SLs in Asian patients.Method: Twenty-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to previous studies, the THG intensity is sensitive to melanin, whereas the melanin mass density of the focal volume is directly related to the intensity of the THG signal in the basal layer. 39 , 70 , 71 , 72 , 73 In this study, although the THG signal was also found to be highly sensitive to the presence of FINEs, the nerve fibers were mostly distributed among the basal keratinocytes, causing them to be easily shadowed by the surrounding background THG from melanin. For patients with diabetic neuropathy, the most common site of symptoms is the distal extremities and with a length-dependent process; thus, areas with a low melanin content on the distal leg are excellent candidate sites for dTHGM.…”
Section: Methodsmentioning
confidence: 56%
“…According to previous studies, the THG intensity is sensitive to melanin, whereas the melanin mass density of the focal volume is directly related to the intensity of the THG signal in the basal layer. 39 , 70 , 71 , 72 , 73 In this study, although the THG signal was also found to be highly sensitive to the presence of FINEs, the nerve fibers were mostly distributed among the basal keratinocytes, causing them to be easily shadowed by the surrounding background THG from melanin. For patients with diabetic neuropathy, the most common site of symptoms is the distal extremities and with a length-dependent process; thus, areas with a low melanin content on the distal leg are excellent candidate sites for dTHGM.…”
Section: Methodsmentioning
confidence: 56%
“…According to a previous study, the THG intensity is sensitive to melanin, while the melanin mass density (MMD) of the focal volume is directly related to the intensity of the THG signal in the basal layer [74]. In this study, although the THG signal was also found to be highly sensitive to the presence of FINEs, nerve fibers are mostly distributed among the basal keratinocytes, causing it to be easily shadowed by the surrounding background THG from melanin.…”
Section: Methodsmentioning
confidence: 64%
“…According to a previous study, the THG intensity is sensitive to melanin, while the melanin mass density (MMD) of the focal volume is directly related to the intensity of the THG signal in the basal layer [74].…”
Section: Imaging Acquisition Area Selection For Clinical In Vivo Tfet...mentioning
confidence: 99%